The product space: What does it say about the opportunities for growth and structural transformation of Sub-Saharan Africa? - Arnelyn Abdon; Jesus Felipe (Levy Economics Institute of Bard College, 2011)
In this paper we look at the economic development of Sub-Saharan Africa (SSA) in the context of structural transformation. We use Hidalgo et al.'s (2007) concept of product space to show the evolution of the region's productive structure, and discuss the opportunities for growth and diversification. The majority of SSA countries are trapped in the export of unsophisticated, highly standard products that are poorly connected in the product space; this makes the process of structural transformation of the region particularly difficult. The products that are nearby to those they already export have the same characteristics. Therefore, shifting to these products will do little to improve SSA's growth prospects. To jump-start and sustain growth, governments must implement policies and provide public inputs that will encourage the private sector to invest in new and more sophisticated activities.
Keywords: O14; O25; O55; 330; industrial policy; product space; structural transformation; Sub-Saharan Africa; Strukturwandel; Wirtschaftswachstum; Wachstumspolitik; Strukturpolitik; Entwicklungspolitik; Afrika südlich der Sahara